Kroppen eller knoppen - en rapport om idrottsgymnasierna
The history of the national sports upper secondary school can be traced back to a number of parliamentary bills on youth sport passed in 1965. These led to a government commission of enquiry which in 1969 (SOU 1969:29) presented the first proposal for a combination of elite sport (i.e. at national/international level) and education. A trial operation initiated in 1972 by the Swedish Sports Federation together with two municipalities was taken over in 1977 by the National Board of Education, allowing changes to be made to the syllabus. The new subject of specialist sport made its first appearance and in 1982 the combination of elite sport and education was established on a permanent basis. The programme was extended throughout the 1980s and start of the 1990s, reaching a high point in 1993/94 when 32 sports had sports upper secondary schools in 49 municipalities, with a total of around 1,800 students in 1992. The number of first-year places was a maximum of 850. The position of the national sports upper secondary school has once again come to the fore in connection with the latest upper secondary school reform. The overall aim is to make it possible for talented youngsters to combine a focus on elite sport with upper secondary school studies. The original objectives stressed social responsibility with only a limited elite sports element. Today`s objectives are more overtly sport-oriented.